Sepsis Management in a Case of Myasthenic Crisis: A Case Report - Hossein Karballaei Mirzahosseini; Ehsan Yousefi-Mazhin; Rezvan Hassanpour; Atabak Najafi; Mahsa Tofighi-Mohammadi; Hamidreza Sharifnia; Amirmahdi Mojtahedzadeh; Mojtaba Mojtahedzadeh (Archives of Anesthesia and Critical Care)
Myasthenic crisis can affect the respiratory muscles in a life-limiting way that requires intubation and mechanical ventilation. This is a case report of a myasthenic crisis in a 61-year-old woman that became complicated following a lack of response to plasmapheresis, intravenous immunoglobulin (IVIG) therapy, and the development of septic shock. The co-occurrence of myasthenic crisis and sepsis is a challenging condition. Many antibiotics cause flare-ups of myasthenia gravis. Infection and sepsis can exacerbate myasthenia. We discuss the successful management of certain unique challenges. To treat sepsis, drugs that may cause deterioration of myasthenia gravis, such as amikacin, ciprofloxacin, colistin, vancomycin, amphotericin B, and voriconazole were prescribed, but eventually the sepsis was cured. After eradicating the infections and stabilizing the patient's hemodynamic, she received rituximab. After 3 weeks of treatment, she responded well to the rituximab, the respiratory failure recovered, and she was extubated and discharged from the ICU after 3 months of hospitalization. This report demonstrates that when the myasthenic patient is under mechanical ventilation, can use even cautionary drugs.